Estimation of Residual Organic Matter and Heavy Metals in Some Hookah (Waterpipe, Argileh) Samples - Hamad Hasan,; Moftah Al Jamal,; Ahlam Mahmoud,; Gibril Al Daik, (AlQalam Journal of Medical and Applied Sciences, 2025)
The residual of organic matter and some heavy metals were estimated in the water of shisha, Hookah samples which were collected from some cafes at Albayda city, the samples including types of shisha Tobacco as Apple normal, Apple vakher, Mint, Salloum, and Blueberry. The spectrophotometer instrument was used to estimate the total organic matter by using potassium hydrogen phthalate (KHP) as a standard, while the heavy metals were determined by atomic absorption. The results of this study showed that the concentrations of organic matter in hookah samples were as follows: the minimum organic matter level was observed in the Apple normal sample (141.41mg/g), while the maximum organic matter level was observed in the Blueberry sample (47.023mg/g). The results indicated that the studied hookah (water pipe or water shisha) samples contained different values of nickel, iron, and copper and ranged between (0.13 - 9.87 mg/g) and (0.24 – 2.32 mg/g), and (0.4 –40 mg/g), respectively. The study concluded that the presence of high values of organic matter and heavy metals gave an indicator for these compounds directly affecting human health, where most of the organic compounds present in tobacco have carcinogenic effects.